Pengaruh Kinerja Pegawai Dan Penggunaan Teknologi Informasi Terhadap Kepuasan Masyarakat (Study Pada UPTD Pengujian Kendaraan Bermotor Dishub Kabupaten Jember) - Asyidiq, Mohammad Madya; Martini, Ni Nyoman Putu; Thamrin, Mohammad (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2023)
In an era of increasingly advanced and developing information technology, the use of technology in various aspects of life has had a significant impact, including in the public service sector. In this context, employee performance and the use of information technology play an important role in providing good satisfaction to society. Good employee performance in service organizations greatly influences community satisfaction. The purpose of this study was to determine directly or indirectly the effect of employee performance and the use of information technology on public satisfaction at the UPTD Motorized Vehicle Testing Department of Transportation, Jember Regency. The number of samples in this study were 230 respondents using the Hair formula. The analysis technique used is SEM using WarpPLS 7.0. The results of the data analysis show that (1) employee performance has a positive and significant effect on community satisfaction, (2) the use of information technology has a positive and significant effect on community satisfaction